(untitled) (Research, Society and Development, 2023)
Introduction: The impact of drug treatment on COVID-19 patients can aggravate the patient’s hyperglycemia, while COVID-19 complications such as endothelial damage caused by inflammation, glucotoxicity and cytokine storm can contribute to the high risk of thromboembolic complications and organ damage in diabetes patients. Objective: To address the influence of gestational diabetes on the worsening of COVID-19. Methodology: It’s an integrative literature review with articles published between 2004 and 2023, through a search on the PubMed platform, in indexed journals with scientific impact, in Portuguese and English. Results: Ten publications were selected and submitted to content analysis. Conclusion: Diabetes and COVID-19 have a mutually aggravating relationship, caused for example by the drugs used to treat COVID-19, by the symptoms of the diseases, by the damage caused to organs that can worsen the condition of the patient and by the difficulties and risks that pregnant women with Gestational Diabetes Mellitus have been subjected to because of this pandemic.